A Survey of Students' Preferences in Doing Assignments - Norhayati, Rosli (Universiti malaysia sarawak (UNIMAS), 2007)
Each individual has different perceptions of doing assignments. Some students think that conducting an assignment was a good experience and some perceive it as a burden. This project looks into student's preference towards doing assignments. The problems faced by the students like low motivation, students not possessing the required skills and experience, accessibility of information, lack of time and resources (information, money) can influence student preference towards assignments. The objectives of this study are to find students' perception towards doing assignments, to discover the relationship between the student skills, lecturers' parents and friends' assistance as well as communication and information accessibility with student preference toward doing assignments and to know which one of these factors is most influential to student preference toward doing assignments. Two hundred questionnaires were distributed to the students of Unimas. Based on the finding, it was discovered that most of the respondents do not prefer to do the assignments. The finding also revealed that communication and information accessibility is correlated with the student's preferences. The most influential factor is communication. As a conclusion, the finding have indicates that most students in UNIMAS do not prefer to do assignments and communication do play an important role in order for the students to achieve better performance in conducting their assignments.